Genetic Variants in IL‐12B and IL‐27 in the Polish Patients with Systemic Lupus Erythematosus. (July 2016) - Paradowska‐Gorycka, A.; Sowinska, A.; Stypinska, B.; Grobelna, M. K.; Walczyk, M.; Olesinska, M.; Piotrowski, P.; Jagodzinski, P. P.
Abstract: To investigate the potential association between IL‐12B and IL‐27 gene polymorphisms and systemic lupus erythematosus (SLE), we performed a case–control study based on the Polish population. Patients with SLE and healthy individuals were examined for −6415 CTCTAA/GC (rs17860508) and +1188A/C (rs3212227) in IL‐12B and −924A/G (rs153109) and 4730T/C (rs181206) in IL‐27 gene polymorphisms using the high‐resolution melting method, PCR–RFLP method and TaqMan SNP genotyping assay, respectively. An increased frequency of GC/GC genotype as well as GC allele of the IL‐12B rs17860508 was found in patients with SLE, as compared with healthy subjects ( P < 0.001). We did not find differences in genotype and allele frequencies of the IL‐12B rs3212227 and IL‐27 rs153109 and rs181206 variants between patients with SLE and controls. IL‐27 haplotype rs181206C/rs153109G indicated higher risk for SLE ( P = 0.002), whereas haplotype rs181206T/rs153109G indicated reduced risk for SLE ( P = 0.005). The IL‐12B rs3212227 A/C polymorphism was associated with the mean value of the platelets (PLT), urea and complement C3 level. Furthermore, IL‐12B rs17860508 genetic variant showed correlation with PLT, prothrombin time, international normalized ratio and alkaline phosphatase. Our results revealed that IL‐12B rs17860508 and IL‐27 haplotype CG are genetic risk factors for SLE and that both IL‐12B rs17860508 and rs3212227 predict disease phenotype.